2016
DOI: 10.5114/fn.2016.58919
|View full text |Cite
|
Sign up to set email alerts
|

Rosette-forming glioneuronal tumour of the fourth ventricle: case report and review of the literature

Abstract: A b s t r a c t Rosette-forming glioneuronal tumour (RGNT) of the fourth ventricle is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Until recently only about 47 cases were reported in the literature with only short follow-up [2, 7]. A review of the literature published by Hakan [9] in 2016 reported only four cases of recurrence. We observed a recurrence in our patient four years after total resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently only about 47 cases were reported in the literature with only short follow-up [2, 7]. A review of the literature published by Hakan [9] in 2016 reported only four cases of recurrence. We observed a recurrence in our patient four years after total resection.…”
Section: Discussionmentioning
confidence: 99%
“…Initially it was described as dysembryoplastic neuroepithelial tumour of the cerebellum arising in relation to the wall of the fourth ventricle, typically in a midline location [6] with possible extension into surrounding structures. Cases involving other sites of the central nervous system including cerebellum, brainstem, pineal region, optic chiasm, hypothalamus, and cervical spinal cord have been reported [1, 2, 69]. In the latest 2016 WHO classification it is recognised as a neural and mixed neuronal glial tumour [10].…”
Section: Introductionmentioning
confidence: 99%
“…These were originally described in the fourth ventricle but have been reported in the chiasm, suprasellar region, pineal gland, and spinal cord. 28 Commoner in females, mean age at diagnosis is 29 years. 28 The commonest presentation is headache followed by ataxia and nystagmus.…”
Section: Neuronal and Mixed Neuronal-glial Tumorsmentioning
confidence: 99%
“…28 Commoner in females, mean age at diagnosis is 29 years. 28 The commonest presentation is headache followed by ataxia and nystagmus. Due to the long-standing nature of the tumor, hydrocephalus may be chronic.…”
Section: Neuronal and Mixed Neuronal-glial Tumorsmentioning
confidence: 99%
See 1 more Smart Citation